IMPROVING ENVIRONMENTAL HEALTH THROUGH REDUCE REUSE RECYCLE (THE 3RS) AND TRASH CANS WITH ATTRACTIVE PICTURES AT HIGH SCHOOL IN PERCUT SEI TUAN SUB-DISTRICT - Naria, Evi; Nasution, Ernawati; Santi, Devi N (Talenta Publisher, 2018)
Waste management should be carried out by implementing the concept of the 3Rs. Waste is generated in various places including in schools. Students frequently do not collect the waste into a trash can and often leave the waste in the schoolyard, desk drawers. Even though the slogan â€œkeep the school cleanâ€ is instructed to the students, but they still often litter the school environment. This activity aims to improve studentsâ€™ litter education in waste management by implementing the 3Rs and providing trash cans with attractive pictures to attract students to collect the waste into the trash cans. The method was participatory method and training to manage waste based on the concept of the 3Rs. The result shows that students were able to manage waste by applying the concept of the 3Rs. Students understood the concepts of the 3Rs, and created some products such as phone stand, hand soap dispenser, and reusable grocery bags. Trash cans with attractive pictures were provided in several areas around the school such as teachersâ€™ room, canteen, and classroom. Students actively participated in waste management by applying the 3Rs. This activity beneficially reduces environmental pollution and simultaneously improves personal autonomy in environmental sustainability.